Pengaruh Stres Kerja dan Mutasi Karyawan Terhadap Kinerja Karyawan pada Bank Syariah Indonesia (BSI) Ujung Batu - Desvi Emti; Hartuti Oktaviani; Umi Rachmah Damayanti (Yayasan Almanar Pujud, 2024)
In Indonesia, banking is a crucial part of the financial infrastructure, the role of banking partners is in collecting funds from the public and providing loans and other financial services. With the rapid growth in the sharia banking industry, the need for Human Resources (HR) who have special expertise in the sharia banking sector seems to be increasing. This research aims to determine the effect of work stress and employee transfers on performance. The research was carried out on employees at Bank Syariah Indonesia (BSI) Ujung Batu. The type of research used in this research is quantitative. The sample consisted of 35 people using the nonprobability sampling technique, total sampling method. The data analysis method in this research uses multiple linear analysis using the IBM SPSS Statistics 25 application. The results of the research show that the Job Stress variable (X1) has a positive and significant influence on performance (Y), and Employee Transfer (X2) has a positive influence and significant to Performance (Y).